What you see is what you hear: The importance of visual priming in music performer identification. (November 2016) - Mitchell, Helen F.; MacDonald, Raymond A. R.
Visual information plays a critical role in the assessment of music performance. Audiovisual integration is well recognised in person perception, and people readily match talking faces to speaking voices. This effect exists in identifying music performers, but its strength is untested. This study investigated the importance of visual or audio priming in identifying a music performer from a line-up. Half the participants saw a target saxophonist (no sound) and then heard a line-up (no visuals) of saxophonists playing (2 to 5 saxophonists). In contrast, half the participants heard a target saxophonist (no visuals) and then saw the line-up (no sound). Participants identified the target saxophonist in visual and audio line-ups at a rate above chance, although identification accuracy decreased as the line-up number increased. Those who saw the targets identified a significantly greater number of performers from the audio line-up than those who heard the targets and identified them from a visual line-up. As the task complexity and number of distractors increased, responses remained consistent and visual priming was robust and reliable in performer identification.